LPS Tolerance Inhibits Cellular Respiration and Induces Global Changes in the Macrophage Secretome - Gillen, Joseph (Biomolecules, 2021)
Inflammatory response plays an essential role in the resolution of infections. However, inflammation can be detrimental to an organism and cause irreparable damage. For example, during sepsis, a cytokine storm can lead to multiple organ failures and often results in death. One of the strongest triggers of the inflammatory response is bacterial lipopolysaccharides (LPS), acting mostly through Toll-like receptor 4 (TLR4). Paradoxically, while exposure to LPS triggers a robust inflammatory response, repeated or prolonged exposure to LPS can induce a state of endotoxin tolerance, a phenomenon where macrophages and monocytes do not respond to new endotoxin challenges, and it is often associated with secondary infections and negative outcomes. The cellular mechanisms regulating this phenomenon remain elusive. We used metabolic measurements to confirm differences in the cellular metabolism of naïve macrophages and that of macrophages responding to LPS stimulation or those in the LPS-tolerant state. In parallel, we performed an unbiased secretome survey using quantitative mass spectrometry during the induction of LPS tolerance, creating the first comprehensive secretome profile of endotoxin-tolerant cells. The secretome changes confirmed that LPS-tolerant macrophages have significantly decreased cellular metabolism and that the proteins secreted by LPS-tolerant macrophages have a strong association with cell survival, protein metabolism, and the metabolism of reactive oxygen species.